Mathematical Models for Estimating Tree Site index for Agar Tree (Aquilaria malaccensis Lamk) Plantations in Bangladesh - Islam, S.M. Zahirul; Chowdhury, M.A. Mansur; Misbahuzzaman, K. (Indian Forester, 2018)
Agar tree (Aquilaria malaccensis Lamk., Family- Thymeleaceae) has drawn unique position due to the production of world’s most expensive essential oil used in fragrances and as medicine. It is one of the most valuable and economically important commercial tree species planted in some potential forest areas of Bangladesh. The aim of this study is to predict site index equation for estimating site quality of Agar tree in Bangladesh by difference equation method. The data have been collected from 372 sample plots with an area 0.02 ha were used to estimate the parameters of the model by means of regression analysis. In total, four (Power model, Schumacher models, Chapman â€“Richards model and Lars strand equation) models were tested to develop site index guide equation for Agar tree. These functions are checked by an examination of statistical and biological principles and by also a comparison with data not used for constructing the functions. The checks gave fairly satisfactory results for Schumacher models, and the model seem suitable for their purpose. Hence, the selected models derived in the study could be satisfactorily used for agar tree plantations having ages 4-20 years and site indices of 8- 20 m. based on a base age of 12 years.